Mixed Methods Design: A Narrative Literature Review - Vesile Alkan; Selçuk Şimşek; Burcu Armağan Erbil (Anı Publishing, 2019)
In this study it is aimed to review the description and structure of mixed methods design along with the research process from conducting to concluding. According to this aim, a narrative literature review technique, a type of literature review, is used. What is mixed methods design, how it is structured and how the process is conducted are theoretically clarified in this study. In addition to this, the points which are taken into consideration while presenting a research planned and conducted as a mixed methods design with mixed methods research's examples gathered from the literature are examined. As a result of review, the rules of mixing qualitative and quantitative research designs in a study designed according to mixed methods research should be considered. The decision of selecting the type of mixed methods designs should be determined. Moreover, mixing rules as timing, priority and integration should be regarded while mixing qualitative and quantitative research. While composing research questions, qualitative, quantitative and mixed methods research questions should be included. The rules of the selected type of mixed methods design should be followed during conducting the research process and concluding the research. A researcher should make the presentation of mixed methods research in terms of given rules.